A comparative evaluation of Aura-OMI and SKYNET near-UV single-scattering albedo products - Jethva, Hiren; Torres, Omar (Atmospheric measurement techniques, 2019)
The aerosol single-scattering albedo (SSA) retrieved by the near-UV algorithm applied to the Aura Ozone Monitoring Instrument (OMI) measurements (OMAERUV) is compared with an independent inversion product derived from the sky radiometer network SKYNET – a ground-based radiation observation network with sites in Asia and Europe. The present work continues previous efforts to evaluate the consistency between the retrieved SSA from satellite and ground sensors. The automated spectral measurements of direct downwelling solar flux and sky radiances made by the SKYNET Sun-sky radiometer are used as input to an inversion algorithm that derives spectral aerosol optical depth (AOD) and single-scattering albedo (SSA) in the near-UV to near-IR spectral range. The availability of SKYNET SSA measurements in the ultraviolet region of the spectrum allows, for the first time, a direct comparison with OMI SSA retrievals eliminating the need of extrapolating the satellite retrievals to the visible wavelengths as is the case in the evaluation against the Aerosol Robotic Network (AERONET). An analysis of the collocated retrievals from over 25 SKYNET sites reveals that about 61 % (84 %) of OMI–SKYNET matchups agree within the absolute difference of ±0.03 (±0.05) for carbonaceous aerosols, 50 % (72 %) for dust aerosols, and 45 % (75 %) for urban–industrial aerosol types. Regionally, the agreement between the two inversion products is robust over several sites in Japan influenced by carbonaceous and urban–industrial aerosols; at the biomass burning site Phimai in Thailand; and the polluted urban site in New Delhi, India. The collocated dataset yields fewer matchups identified as dust aerosols mostly over the site Dunhuang with more than half of the matchup points confined to within ±0.03 limits. Altogether, the OMI–SKYNET retrievals agree within ±0.03 when SKYNET AOD (388 or 400 nm) is larger than 0.5 and the OMI UV Aerosol Index is larger than 0.2. The remaining uncertainties in both inversion products can be attributed to specific assumptions made in the retrieval algorithms, i.e., the uncertain calibration constant, assumption of spectral surface albedo and particle shape, and subpixel cloud contamination. The assumption of fixed and spectrally neutral surface albedo (0.1) in the SKYNET inversion appears to be unrealistic, leading to underestimated SSA, especially under lower aerosol load conditions. At higher AOD values for carbonaceous and dust aerosols, however, retrieved SSA values by the two independent inversion methods are generally consistent in spite of the differences in retrieval approaches.